Pretreatment with Ozone Elevates the Resistance of Saccharomyces cerevisiae Yeast Membranes during Freeze-Thawing - Zinchenko, Vasiliy D.; Goryachaya, Irina P.; Buryak, Irina A.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2014)
Тhe effect of ozone on injury of Saccharomyces cerevisiae yeast membranes following freezing (down to –196°C) and warming (up to 30°C) was investigated using fluorescent staining and flow cytometry. It has been shown that freeze-thawing of S. cerevisiae cells in physiological solution resulted in the injury of membranes in 65.6% of total cells population. Treatment of the cells with ozone in a dose of 29–240 рmol О3/106 cells prior to freezing allowed to reduce significantly the number of damaged cells: (16.1 ± 0.9)% of total population. The observed effect was explained by cross-adaptation caused by ozone introduction: the adaptive response to slight oxidative stress initiated the genetically determined mechanisms of responces to other stresses, including the one caused by freeze-thawing. Probl Cryobiol Cryomed 2014; 24(1):38–46.